Cork wastes as energy sources - Gil, Luís (2014)
This work shows the possibility of using cork wastes form cork processing for energy production. In cork processing operations an important waste is produced, cork powder, the main waste of the cork industry, which is estimated to reach over 30000 tons/year. There are various types of cork powders with higher calorific values ranging from 4,000-7,000 Kcal/kg. This powder is commonly burned to produce steam or heat used in the factories themselves, given the high energy content of this material. As an example, a cork company of a large industrial group that produces cork products for construction meets 60% of its energy needs using waste cork. Cork boiling wastewater (CBW) is an aqueous and complex effluent of the cork industry which is produced during the boiling of the cork planks. CBW contains organic materials such as phenolic. This boiling wastewater has no utility, being a serious environmental hazard. Anaerobic digestion is a promising technology for the treatment of organic effluents and for the simultaneous recovery of its energetic potential through methane production. Its application to cork effluents was studied. An anaerobic assay was conducted. The resultant methane potentials were 0.126 - 0.142 m3 CH4 kg-1 COD. The calculated total volume of CBW produced yearly in Portugal is 30 374 m3. As 1 m3 of CBW (6,5 COD kg m-3) in cogeneration can produce in average 1,72 kWh of electric energy and 3,73 kWh of thermal energy, the total CBW volume produced in Portugal in one year corresponds to a total energy value of 165 400 kWh.